2020
DOI: 10.1093/mnras/staa011
|View full text |Cite
|
Sign up to set email alerts
|

Embedding globular clusters in dark matter minihaloes solves the cusp–core and timing problems in the Fornax dwarf galaxy

Abstract: We use a fully GPU N-body code to demonstrate that dark matter minihalos, as a new component of globular clusters, resolves both the timing and cusp-core problems in Fornax if the five globular clusters were recently accreted (2-4 Gyr ago) by Fornax. Under these assumptions, the infall of these globular clusters does not occur and no star clusters form in the centre of Fornax in accordance with observations. Crossings of globular clusters with a DM minihalo near the Fornax centre induce a cusp-to-core transiti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 69 publications
2
38
0
Order By: Relevance
“…For the galactic center of Fornax we use an updated measurement [20], based on surface brightness modelling. This estimate is ≈ 160 pc off relative to the center defined by previous works [2,16,18,29,31,44], leading to different projected radii of GCs. We set the distance to Fornax as 147 ± 4 kpc [17].…”
Section: Dynamical Friction In a Cdm Halo: Core Vs Cuspmentioning
confidence: 72%
See 1 more Smart Citation
“…For the galactic center of Fornax we use an updated measurement [20], based on surface brightness modelling. This estimate is ≈ 160 pc off relative to the center defined by previous works [2,16,18,29,31,44], leading to different projected radii of GCs. We set the distance to Fornax as 147 ± 4 kpc [17].…”
Section: Dynamical Friction In a Cdm Halo: Core Vs Cuspmentioning
confidence: 72%
“…Many explanations were suggested for the GC timing puzzle [22][23][24][25][26][27][28][29][30][31][32][33][34][35], of which an exciting class of ideas entails a modification to the nature of dark matter, going beyond CDM [29,[32][33][34][35]. In particular, Refs.…”
Section: Nfw Gc4mentioning
confidence: 99%
“…This simple model suggests that only one GC, Frn 4, was born at a small radial distance, r init = 700 pc, which is approximately the half-light radius of the present-day Fornax (as given by McConnachie 2012). For the remaining four GCs, the initial distances are larger than 1.5 kpc, which suggests that at least some of them were accreted (see also Boldrini et al 2020). This result is in good agreement with our model prediction that around half of the present-day surviving GCs are of accreted origin.…”
Section: Past and Future Orbits Of The Gcs In Fornaxmentioning
confidence: 99%
“…Another possibility has been proposed by Boldrini, Mohayaee & Silk (2020) who have shown that if the GCs are surrounded by their own DM minihaloes, then there is no 'GC timing problem' even in cuspy haloes. Finally, it is worth mentioning that tidal streams produced by the disruption of GCs stripped from dwarf galaxies can perhaps be used to distinguish between a central cusp or a core in the halo of the dwarf from which the GC was stripped (Malhan, Valluri & Freese 2020).…”
Section: ; DImentioning
confidence: 99%
“…One possibility is that some halo clusters formed at or near the center of small dark matter halos. Tidal fields in an assembling galaxy later remove the outer dark matter, but clusters can retain dark matter within their tidal radii to the present day (Ibata et al 2013;Boldrini et al 2020;Carlberg & Keating 2021). An example is the cluster NGC 6715 (M54), located at the center of the Sagittarius dwarf galaxy, an accreted dwarf galaxy being dispersed into the Milky Way (Ibata et al 1997;Vasiliev & Belokurov 2020).…”
Section: Introductionmentioning
confidence: 99%